Pengaruh Return on Asset, Ukuran Perusahaan dan Financial Leverage terhadap Tindakan Perataan Laba (Studi Empiris Pada Perusahaan Sektor Keuangan yang Terdaftar di BEI) - Kurniawan, MS; Latifah, Sri Wahjuni; Zubaidah, Siti (Journal of Accounting and Investment, 2012)
The aimed of this study was to examine the influence of company's characterictics toward income smoothing practice among listed companies at Indonesian Stock Exchange. The factors being examined were return on asset, company size and financial leverage. Index Eckel is used to determine the income smoothing practice. The study was using 43 finance companies listed at Indonesian Stock Exchange, with a period between 2006-2010. The hypothesis was tested using multiple regression. The first hypothesis was used to examine the influence of return on asset to income smoothing practice. The second hypothesis was used to examine the influence of company size to income smoothing practice. The third hypothesis was used to examine the influence of financial leverage to income smoothing practice. The result of this study indicated that 20 out of 43 companies which were used as samples committed income smoothing practices. The output of multiple regression showed that return on asset having a significant influence to income smoothing practice. But company size and financial leverage did not have influence to income smoothing practice.Â